Analysis of potential post-quantum mechanisms of electronic signatures based on hash functions - Горбенко, Ю.І.; Мельник, Т.В.; Горбенко, І.Д. (Radiotekhnika, 2017)
The results of the analysis of electronic signatures with one-time keys for the post-quantum period are given. The requirements are justified and an improved mechanism of electronic signature is presented for the criteria of spatial complexity of keys and signatures. A model of the violator and threats is proposed. The main types of attacks on the electronic signature with one-time keys are substantiated. The main relations of the post-quantum cryptanalysis complexity estimation are presented. The main recommendations and the main spheres of using the electronic signature in the post-quantum period are given.